ROLE-PLAYING TO IMPROVE SPEAKING ABILITY AMONG STUDENTS - Yudiati, Rini; Anni Annisa (Bajang Institute, 2024)
English as a foreign language in Indonesia is taught at University as MKU (Mata Kuliah Umum) public course. The implementation of English teaching at present is based on the Content Standard. Its target is to have the students reach an informational level of literacy. The objective of the sudy is intended to describe how the speaking ability of the third semester of teaching and science education department be improved through role-playing technique. The design of this study was classroom action research and used 2 cycles. This design will be chosen since this study dealt with the classroom setting and the study was directed to implement the teaching technique in that specific class in order to find out solutions to the classroom problems in the teaching of speaking. In conducting this research, the researcher worked collaboratively. The result are the researcher implemented 7 (seven) major steps in the procedure for the role play activities. First, the teacher decides on the teaching materials. The second step is organizing the group of the students. The third step is providing the situation and dialogue to be role played. The forth step applied by the researcher in implementing role-playing technique is explaining the situation in the cue card as well as the dialogue. The fifth step is having the students practice the role plays. The sixth step is having students modify the situation and dialogue. The last step is having the students perform the dialogue in front of the class.